Religious identity as a contributing factor of the integration of Middle Eastern immigrants into the Croatian society - Eva Katarina Glazer; Erik Brezovec (Ignatianum University Press, 2019)
The migrant crisis in Europe is one of the most challenging problems that European Union has faced since its very existence. By examining the process of acculturation of Middle Eastern migrants in Zagreb this paper will provide a basic insight in this cultural phenomenon. The possibilities of the successful integration lies within the religious identity of Islam as partially common both to migrants and Muslim population in Croatia. Another positive factor for the successful integration can be found in the history of Muslim population in Croatia whose rich tradition and integration in the Croatian society can been regarded as highly instructive. The main goal of the paper is to present the experience of the encounters that individuals from the Islamic Centre in Zagreb had with the Immigrants from Middle East through the qualitative methodology and the deep interview method. This research should provide better understanding of the importance of religious identity in the process of integration of Middle East migrants in the European society and guidelines for overcoming the risks of parallel societies. In addition the authors will present an overview of the problems that occur in education process in the context of religious identities, with an emphasis on Islam in Croatian educational system.